Desafíos en la implementación de la custodia compartida: desarrollo jurisprudencial en Colombia - Diaz Granados Barros, Virginia Beatriz (Universidad Antonio Nariño, 2021)
The challenges of implementing joint custody in the legal systems of Spain, Chile and Puerto Rico make it possible to see the possible problems that its implementation suppose in the Colombian legal system. However, the challenges encountered in other legal systems have been resolved in case law by the Supreme Court of Justice and the Constitutional Court in Colombia. Thus, although not fully regulated, the best interests of children and young persons and the fundamental right to have a family and not be separated from it, have guided analyses of the implementation of joint custody in various cases, thus ensuring the rights and interests of children and young persons